Perinatally acquired HIV infection is associated with abnormal blood mitochondrial function during childhood/adolescence. (15th July 2021) - Jao, Jennifer; Jacobson, Denise L.; Russell, Jonathan S.; Wang, Jiajia; Yu, Wendy; Gojanovich, Greg S.; Siminski, Sue; Hyzy, Laurie; Geffner, Mitchell E.; Gerschenson, Mariana
Abstract : Objective: We assessed differences in mitochondrial function between youth living with perinatal HIV (YPHIV) and youth perinatally HIV-exposed but uninfected (YPHEU). Design: Cross-sectional analysis. Methods: We measured lactate and pyruvate values, as well as mitochondrial Complex I and Complex IV activity in peripheral blood mononuclear cells. Logistic or linear regression models were fit, as appropriate, to assess the association between PHIV status and each mitochondrial parameter, adjusted for confounders. We introduced interaction terms to assess effect modification of PHIV status on the relationship between anthropometric factors and each mitochondrial parameter. Among YPHIV, similar regression models were fit to assess the relationship between HIV-associated factors and each mitochondrial outcome. Results: A total of 243 YPHIV and 118 YPHEU were compared. On average, YPHIV had higher lactate/pyruvate ratio ( β : 7.511, 95% confidence interval [95% CI]: 0.402, 14.620) and Complex IV activity ( β : 0.037, 95% CI: 0.002, 0.072) compared to YPHEU, adjusted for confounders. Among YPHIV, body mass index Z score (BMIZ) and Complex I activity were inversely associated, whereas, among YPHEU, there was a positive association ( β for interaction: −0.048, P  = 0.003). Among YPHIV, current ( β : −0.789, 95% CI: −1.174, −0.404) and nadir CD4 + % ( β : −0.605, 95% CI: −1.086, −0.125) were inversely associated with lactate/pyruvate ratio; higher current (4.491, 95% CI: 0.754, 8.229) and peak (7.978, 95% CI: 1.499, 14.457) HIV RNA levels were positively associated with lactate/pyruvate ratio in adjusted models. Conclusions: Mitochondrial function and substrate utilization appear perturbed in YPHIV compared to YPHEU. Increasing immunosuppression and viremia are associated with mitochondrial dysfunction among YPHIV.